2014
DOI: 10.1159/000358097
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury: An Emotion Regulation Perspective

Abstract: Background: Nonsuicidal self-injury (NSSI) is widely thought to serve an emotion-regulatory function. Method: The focus of the present paper is to provide a conceptual framework for understanding how NSSI might modify a person's emotions. Results: Drawing upon the process model of emotion regulation, we argue that 5 families of emotion regulation strategies may be engaged by NSSI. Individuals may engage in NSSI as an alternative to more distressing situations. They also may use NSSI to modify their social envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 100 publications
(177 reference statements)
2
59
0
2
Order By: Relevance
“…It further suggests that BSD + NSSI feel more connected to their social environment than BSD + SA, wherefore their self-injurious behavior may function as a cry for help, while BSD + SA may not believe that significant others are able to help them. Nevertheless, the present study was not able to determine whether these traits compel BSD patients to engage in NSSI or SA or if engaging in these behaviors isolates them from others, because of feelings of shame or guilt, as prior research has reported (Mckenzie and Gross, 2014). Unlike previous studies (Claes et al, 2012), the present study found no differences between groups in harm-avoidance and self-directedness.…”
Section: Discussionmentioning
confidence: 66%
“…It further suggests that BSD + NSSI feel more connected to their social environment than BSD + SA, wherefore their self-injurious behavior may function as a cry for help, while BSD + SA may not believe that significant others are able to help them. Nevertheless, the present study was not able to determine whether these traits compel BSD patients to engage in NSSI or SA or if engaging in these behaviors isolates them from others, because of feelings of shame or guilt, as prior research has reported (Mckenzie and Gross, 2014). Unlike previous studies (Claes et al, 2012), the present study found no differences between groups in harm-avoidance and self-directedness.…”
Section: Discussionmentioning
confidence: 66%
“…Research suggests emotion dysregulation is predictive of suicidal ideation (Arria et al, 2009;O'Connor & Nock, 2014). Some studies investigate disorders associated with emotion dysregulation and their relationship to suicidal ideation and/or attempts, including depression (Mościcki, 2001); substance use disorder (Fischer, Anderson, & Smith, 2004;Mościcki, 2001;Sher & Stanley, 2008); borderline personality disorder (Brown, Comtois, & Linehan, 2002;Selby & Joiner, 2009); anxiety disorders, and PTSD (Elbogen et al, 2017;Gradus et al, 2010); and nonsuicidal self-injury (NSSI; Anestis, Kleiman, Lavender, Tull, & Gratz, 2014;McKenzie & Gross, 2014). However, studies directly examining emotion dysregulation and suicide attempts are less conclusive: While several find the most common reasons given for attempts include escaping or obtaining relief from emotional distress (Brown et al, 2002;Bryan, Hernandez, et al, 2013;Bryan & Rudd, 2012;Bryan, Rudd, & Wertenberger, 2013), others find no correlation between emotion dysregulation and suicidal behavior (Garnefski, Kraaij, & Spinhoven, 2001;Tamás et al, 2007).…”
Section: The Role Of Emotion Dysregulation In Suicidementioning
confidence: 99%
“…Although strong evidence exists for the association of self‐harm with regulation of emotions (Bentley et al., ; Klonsky, ; Mikolajczak, Petrides, & Hurry, ; Perez, Venta, Garnaat, & Sharp, ), there has been a lack of explicit assessment of emotional regulation in the development of self‐harm and a tendency to view emotional regulation in discrete terms (Cole, ; Mckenzie & Gross, ). Emotion‐generative theories suggest a linear process of emotion (Gross, ) in which emotional cues are subject to monitoring and evaluation early in the processing of emotions and have implications for later attempts at emotional modulation (Thompson & Calkins, ).…”
mentioning
confidence: 99%